Political philosophy - Smith, Steven B., 1951- (Open Yale Courses., 2012)
Who ought to govern? Why should I obey the law? How should conflict be controlled? What is the proper education for a citizen and a statesman? These questions probe some of the deepest and most enduring problems that every society confronts, regardless of time and place. Today we ask the same crucial questions about law, authority, justice, and freedom that Plato, Aristotle, Machiavelli, Hobbes, Locke, Rousseau, and Tocqueville faced in previous centuries.